Adolescência e ansiedade: interfaces com a Educação - Silva, Matheus Henrique da (Universidade Federal de São Carlos, 2023)
Adolescence is a phase characterized by numerous changes, covering bodily, cultural and psychosocial aspects that can be related to situations of mental illness, in particular, symptoms related to anxiety. This work aims to address the relationship between adolescence, anxiety and education, considering dimensions related to the development and school life of adolescents (specifically high school students), with a view to focusing on theoretical assumptions related to these themes and their possible connections. For that, a narrative review was carried out (ROTHER, 2007). The following topics are addressed: concept and historical context of adolescence; puberty and psychosocial aspects of adolescent development; anxiety and adolescence, historical aspects of education and school; and about the adolescent’s school life. It discusses the importance of carrying out proposals for the prevention and awareness of anxiety in schools, monitoring and offering the necessary specialized support to adolescents who have difficulties in dealing with the pressures and conflicts that may arise at this stage and during their schooling, seeking to create possibilities for the psychosocial strengthening of this subject and his better integration into society. It is concluded that adolescence is historically constituted in social and economic relations and is not made in biological changes, with the experience of adolescents being marked by the biases of capitalist society and man’s behavior in contemporary times.
Adolescence and anxiety: interfaces with Education
Keywords: Adolescência; Ansiedade; Educação Escolar; Adolescence; Anxiety; School Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO